Profil Faktor Risiko Penderita Stridor Paska Intubasi Pada Anak dengan Kecurigaan Stenosis Subglotis di RSUD Dr. Saiful Anwar Malang Periode 1 Januari – 31 Desember 2017 - Sitompul, Bobby Pardomuan; Murdiyo, Mohammad Dwijo (Malang Otorhinolaryngology Head and Neck Surgery Journal, 2022)
ABSTRACTBackground: Subglottic stenosis (SGS) is a decrease in the width of the subglottic. Although it can be congenital, 90% of the SGS are acquired with intubation and mechanical respiratory assistance being the main cause. The risk factors that cause SGS are poorly understood. Purpose: To identify risk factors on post-intubation stridor patient with suspicion of subglottic stenosis to assist prevention and optimal management strategies. Methods: Retrospective descriptive study with subject of the study are medical records of post-intubation stridor patient in children that have been suspected subglottic stenosis at otorhinolaryngology head and neck surgery departement of Saiful Anwar General Hospital Malang from January 1st until December 31st 2017 Result: The study included 12 subjects. Male to female ratio 3:1, highest distribution 0-1 years old group 50%, aterm pregnancy age 83.3%, normal birth weight 75%, intubation frequency > 1 times 58,3%, duration of intubation > 7 days 66,7%, central nervous system as main disease 41,7%, underwent tracheostomy 33,3%, underwent endoscopic diagnosis 41,7% with 100% suffer subglottic stenosis with various severity. Conclusion: Incidence of post-intubation subglottic stenosis in children is quite high and needs further investigation to identify risk factors.Keyword: Stenosis subglottic in children, risk factors post-intubation